Low-Intensity Focused Ultrasound Alleviates Chronic Neuropathic Pain-Induced Allodynia by Inhibiting Neuroplasticity in the Anterior Cingulate Cortex. (23rd July 2022) - Wang, Bin; Chen, Mo-Xian; Chen, Shao-Chun; Feng, Xiang-Jun; Liao, Ye-Hui; Zhao, Yun-Xin; Tie, Jin-Shan; Liu, Yao; Ao, Li-Juan
Abstract : Low-intensity focused ultrasound (LIFU) is a potential noninvasive method to alleviate allodynia by modulating the central nervous system. However, the underlying analgesic mechanisms remain unexplored. Here, we assessed how LIFU at the anterior cingulate cortex (ACC) affects behavior response and central plasticity resulting from chronic constrictive injury (CCI). The safety of LIFU stimulation was assessed by hematoxylin and eosin (H&E) and Fluoro-Jade C (FJC) staining. A 21-day ultrasound exposure therapy was conducted from day 91 after CCI surgery in mice. We assessed the 50% mechanical withdrawal threshold (MWT50 ) using Von Frey filaments (VFFs). The expression levels of microtubule-associated protein 2 (MAP2), growth-associated protein 43 (GAP43), and tau were determined via western blotting (WB) and immunofluorescence (IF) staining to evaluate the central plasticity in ACC. The regions of ACC were activated effectively and safely by LIFU stimulation, which significantly increased the number of c-fos-positive cells (P < 0.05 ) with no bleeding, coagulative necrosis, and neuronal loss. Under chronic neuropathic pain- (CNP-) induced allodynia, MWT50 decreased significantly (P < 0.05 ), and overexpression of MAP2, GAP43, and tau was also observed. After 3 weeks of treatment, significant increases in MWT50 were found in the CCI+LIFU group compared with the CCI group (P < 0.05 ). WB and IF staining both demonstrated a significant reduction in the expression levels of MAP2, GAP43, and tau (P < 0.05 ). LIFU treatment on ACC can effectively attenuate CNP-evoked mechanical sensitivity to pain and reverse aberrant central plasticity.